2016
DOI: 10.1007/s00264-016-3266-4
|View full text |Cite
|
Sign up to set email alerts
|

Postural stability after patient-specific interpositional knee spacer or total knee arthroplasty: a comparative study

Abstract: The successful treatment of knee osteoarthritis can restore postural stability to the level of the unaffected side-independent from the implanted devices and with preservation of soft tissue and bone stock. Superior postural stability in joint-preserving patient-specific interpositional knee devices compared with total knee arthroplasty had to be attributed to the different age of both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Statistical differences were found in the evaluations of the anterior drawer test, Lachman test and pivot-shift test ( 35 37 ), while no significant differences in the maximum flexion degree of the knee, and the circumference of the thigh and calf, were observed. The results indicated that one-quarter ACL injury may cause instability of the knee joint when ligaments and muscles around the knee joint do not compensate to maintain the stability of the joint ( 38 41 ), which reflected the main characteristics of the model. At the same time, it is notable that short-term instability of knee will not lead to atrophy of the muscles of the hind limb and decreased flexion of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical differences were found in the evaluations of the anterior drawer test, Lachman test and pivot-shift test ( 35 37 ), while no significant differences in the maximum flexion degree of the knee, and the circumference of the thigh and calf, were observed. The results indicated that one-quarter ACL injury may cause instability of the knee joint when ligaments and muscles around the knee joint do not compensate to maintain the stability of the joint ( 38 41 ), which reflected the main characteristics of the model. At the same time, it is notable that short-term instability of knee will not lead to atrophy of the muscles of the hind limb and decreased flexion of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…In a second study, we were able to show that there were no significant differences between implantation of a knee spacer and total knee replacement [15]. …”
Section: Introductionmentioning
confidence: 99%